(untitled) (Dhaka University Journal of Science, 2020)
This paper focused on the analysis of malnutrition of the children of Bangladesh urban areas in the presence of multicollinearity among the covariates. The ridge regression has been adopted under binary logistic model for analyzing malnutrition data extracted from Bangladesh Urban Health Survey 2013 (UHS 2013) dataset. The study reveals that city corporation slum area, mother’s age at birth, gender of child, birth order number, age of child, wealth index, mother’s education, access to media, toilet facility at household, taking antenatal care service, and place of delivery of index child have significant impact on the nutritional status of urban children of Bangladesh. Some recommendations have been suggested for policy makers to improve the child health of urban areas in Bangladesh. Dhaka Univ. J. Sci. 68(1): 13-18, 2020 (January)